The Role of Physics Teacher's Pedagogical Competence in the Implementation of the 2013 Curriculum at SMA Negeri 5 Maros - Karmila Karmila; Kaharuddin Arafah; Muhammad Arsyad (Universitas Muhammadiyah Makassar, 2020)
This study aims to analyze the role of physics teacher pedagogical competencies in the implementation of the 2013 curriculum at SMA Negeri 5 Maros. Besides, to find out the factors that constrain and support the physics teacher's pedagogical competence in implementing the 2013 curriculum at SMA Negeri 5 Maros. To achieve this goal, research has been conducted with a qualitative approach. The subjects of this study were physics teachers at Maros 5 Public High School who had educator certificates. Research data collection using observation techniques, interview guidelines, and documentation. Data were analyzed using the Miles and Huberman technique consisting of data reduction, data presentation, concluding, and verification. The results showed that the physics teacher's pedagogical competence at Maros 5 High School in applying the 2013 curriculum out of the seven aspects that had to be mastered, the teacher was able to master the four aspects that were by the Minister of Education Regulation No. 16 of 2007 concerning Academic Qualification Standards and Teacher Competencies. These inhibiting factors are less than optimal training on increasing competencies for teachers, and lack of time in preparing lesson plans. While the supporting factors of this research are the existence of MGMP which is a place to increase teacher professionalism and teaching materials in the form of curriculum books in 2013.